INFORMATION-EDUCATIONAL ENVIRONMENT ON PHYSICS AS A MEANS FOR SHAPING SELF-EDUCATIONAL SKILLS OF STUDENTS OF TECHNICAL COLLEGES (Journal of Information Technologies in Education (ITE), 2011)
The article examines a structure and functions of the electronic information-educational environment on physics, intended for shaping skills and abilities for self-educational activity of students of technical colleges. Certain methodological recommendations on its use are provided.
Keywords: information-educational environment; skills and abilities of self-educational activity; technical colleges